2019
DOI: 10.1111/tpj.14419
|View full text |Cite
|
Sign up to set email alerts
|

The MYB5‐driven MBW complex recruits a WRKY factor to enhance the expression of targets involved in vacuolar hyper‐acidification and trafficking in grapevine

Abstract: † These authors contributed equally to this work. SUMMARYThe accumulation of secondary metabolites and the regulation of tissue acidity contribute to the important traits of grape berry and influence plant performance in response to abiotic and biotic factors. In several plant species a highly conserved MYB-bHLH-WD (MBW) transcriptional regulatory complex controls flavonoid pigment synthesis and transport, and vacuolar acidification in epidermal cells. An additional component, represented by a WRKY-type transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 80 publications
(147 reference statements)
1
37
0
Order By: Relevance
“…The pK7WG2.0 vectors containing 35S:VviNAC33, VviNAC33-EAR or the eGFP sequence (negative control) were transferred to A. tumefaciens strain EHA105 by electroporation. The genetic transformations were performed as described by Amato et al (2019).…”
Section: Transgenic Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pK7WG2.0 vectors containing 35S:VviNAC33, VviNAC33-EAR or the eGFP sequence (negative control) were transferred to A. tumefaciens strain EHA105 by electroporation. The genetic transformations were performed as described by Amato et al (2019).…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…The VviNAC33 (1320 bp), SGR1 (1558 bp), ATG8f (1616 bp), RopGEF1 (1604 bp), PIN1 (1637 bp) and ATPC1 (1573 bp) promoter regions were amplified by PCR from cv Corvina genomic DNA using KAPA HiFi DNA polymerase. The cloning steps and Dual Luciferase Reporter Assay were carried out as described by Amato et al (2019), using as effector vectors 35S: VviNAC33 with 35S:VviWRKY19 (VIT_07s0005g01710) and 35S:VvibHLH75 (VIT_17s0000g00430), both previously reported by Fasoli et al (2018). Mean AE SD of four biological replicates was calculated.…”
Section: Dual Luciferase Assaymentioning
confidence: 99%
“…These compounds are also found in vegetables and seeds of different crops, but in lower concentrations [6,7]. In plants, 2 of 14 polyphenols are secondary metabolites participating in plant protection from a wide range of biotic and abiotic stress factors [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Petunia PH3 and Arabidopsis TTG2, homologous to kiwifruit WRKY44, were able to bind to the WD40 protein of the MBW complex and formed a MBW-W complex required to transcriptionally activate the target genes involved in vacuolar acidification (petunia) and hair development (Arabidopsis 39 ). In grapevine, VvWRKY26, a homologue of petunia PH3 and AtTTG2, is recruited specifically by the VvMYB5a driven MBW complex to enhance the expression of target genes involved in vacuolar acidification, probably via the formation of a MBW-WRKY complex 40 . In kiwifruit, WRKY motifs are located in close proximity to the MYB and bHLH binding motifs on F3′H and F3′5′H promoters, suggesting the possible binding of the MBW-WRKY complex on the promoters for transcriptional activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In petunia flower petals, the gene PH3 encodes for a WRKY TF that is highly similar to Arabidopsis TTG2, and regulates vacuolar acidification by binding to the MBW complex that transcriptionally activates a vacuolar ATPase 39 . Further investigation has revealed that the grape VvWRKY26, a homologue to petunia PH3 and Arabidopsis TTG2, is recruited by the VvMYB5a to form a MBW-WRKY complex and enhances the transcription of a set of target genes that are involved in vacuolar hyper-acidification 40 . The VvMYB5 gene competes with the anthocyanin activator VvMYBA in the MBW complex and reduces its ability to promote anthocyanin accumulation.…”
Section: Introductionmentioning
confidence: 99%